Review of top charge asymmetries for LHC run II - Westhoff, Susanne (Arxiv, 2017)
This is a brief review of charge asymmetries in top-antitop quark production at the LHC. Proposed asymmetry observables in processes of associated top-pair production $t\bar t$ + jet, $t\bar t + W$, and $t\bar t + γ$ are analyzed and compared. While the focus is on standard-model predictions, we also comment on the sensitivity to possible new physics and observation prospects during the second runtime of the LHC.